2002
DOI: 10.1161/01.atv.0000038485.94020.7f
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of ApoA-I as Lipid-Free Protein or as Component of Discoidal and Spherical Reconstituted HDLs

Abstract: Objective-Apolipoprotein (apo)A-I exists in 3 forms in plasma: as lipid-free apoA-I, as a component of pre-␤-migrating discoidal high density lipoproteins (HDLs), and as a component of ␣-migrating spherical HDLs. This study investigates (1) the in vivo metabolism of apoA-I in each of these forms and (2) the effects of hepatic lipase (HL) on apoA-I metabolism. Methods and Results-Wild-type and HL transgenic rabbits were studied. When lipid-free 125 I-apoA-I and 125 I-apoA-I in pre-␤-migrating discoidal reconsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…3 and 4). Our results are consistent with those of other investigators who have observed rapid assimilation of synthetic pre␤ HDL particles into the medium HDL size range (53,58). However, in the previous studies, only homogeneous medium-sized HDL particles were present in mouse plasma, whereas in hA-I Tg mice, there are abundant large and small HDL particles (29,59).…”
Section: Discussionsupporting
confidence: 94%
“…3 and 4). Our results are consistent with those of other investigators who have observed rapid assimilation of synthetic pre␤ HDL particles into the medium HDL size range (53,58). However, in the previous studies, only homogeneous medium-sized HDL particles were present in mouse plasma, whereas in hA-I Tg mice, there are abundant large and small HDL particles (29,59).…”
Section: Discussionsupporting
confidence: 94%
“…This amount, when given to a 3-kg rabbit (plasma volume approximately 120 mL), would have increased the plasma apoA-I concentration in the immediate postinfusion period by 0.2 mg/mL, an increase of only 40% over the preinfusion concentration of 0.5 mg/mL. Furthermore, with a fractional catabolic rate for rabbit plasma apoA-I of 0.8 pools/d, 44 it would be predicted (as observed) that the apoA-I concentration would have returned to preinfusion levels by the time of euthanasia 24 hours after the last infusion. Yet despite what was no more than a minor and transient increase in the concentration of plasma HDL, the infusions resulted in an almost complete inhibition of the collar-induced arterial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There is also mounting evidence that assembly of most HDL particles occurs at the cell surface (45,(58)(59)(60)(61)(62)(63)(64) or in a recycling endosomal compartment by ABCA1 (65)(66)(67)(68)(69)(70) and not in the secretory pathway of the endoplasmic reticulum and Golgi apparatus (71). Because we have shown that poorly lipidated apoA-I (i.e., pre-b1 HDL) is rapidly catabolized by the kidney, whereas lipid-free apoA-I rapidly and quantitatively transfers to plasma HDLs (17,51), newly synthesized apoA-I from hepatocytes or intestinal epithelial cells has several metabolic fates. If apoA-I escapes lipidation in the secretory pathway and at the cell surface by ABCA1, it is likely to associate with mature HDL particles after entering the circulation (17,51).…”
Section: Discussionmentioning
confidence: 99%
“…Because we have shown that poorly lipidated apoA-I (i.e., pre-b1 HDL) is rapidly catabolized by the kidney, whereas lipid-free apoA-I rapidly and quantitatively transfers to plasma HDLs (17,51), newly synthesized apoA-I from hepatocytes or intestinal epithelial cells has several metabolic fates. If apoA-I escapes lipidation in the secretory pathway and at the cell surface by ABCA1, it is likely to associate with mature HDL particles after entering the circulation (17,51). If lipidation in the secretory pathway or at the cell surface by ABCA1 is sufficient to form pre-b2, -3, or -4 HDLs, these particles will undergo further lipidation by non-ABCA1-mediated pathways and ultimately be converted to mature plasma HDL particles by LCAT in plasma.…”
Section: Discussionmentioning
confidence: 99%